Evaluation of renal function in subclinical and overt hypothyroidism - Badyal, Ashima; Kumar, Sanjeev; Chander, Kailash (International Journal of Research in Medical Sciences, 2019)
Background: Thyroid hormones can cause significant changes in renal function such as decrease in sodium re-absorption in the proximal tubules, impairment in the concentrating and diluting capacities of the distal tubules, a decrease in the urinary urate excretion and a decrease in the renal blood flow and glomerular filtration rate (GFR). This study was therefore planned to analyse the changes in biochemical markers of renal function in patients with subclinical and overt hypothyroidism and to correlate these values with the thyroid profile of the patients with an aim to determine whether thyroid dysfunction has deleterious effects on renal function. Methods: Study was conducted on 200 patients, in the age group of 20-70 years, in the Department of Medicine, in collaboration with Department of Biochemistry, GMC Jammu over a period of 6 months. After centrifugation, the serum was divided into 2 aliquots: one for renal function tests and the other for thyroid function tests. Results: Age wise, mean was found to be 33.2±9.3 years for euthyroid group and 42.8±8.7 years for hypothyroid group. Patients with both subclinical hypothyroidism and overt hypothyroidism showed statistically significant rise in TSH levels as compared to controls. Conclusions: It was seen that primary hypothyroidism is associated with a reversible elevation of serum creatinine in adults as well as children. It is believed that renal impairment with hypothyroidism is due to reduced cardiac output and increased systemic and renal vasoconstriction leading to reduced renal blood and plasma flow and decreased GFR.